2004
DOI: 10.1021/ma0357164
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Polymer Brush with Hydrogen Bonds:  Structure and Orientation Behavior

Abstract: The structure and properties of the H-bonded liquid crystalline (LC) polymer grafted onto fluorocarbon polymer substrate were studied by the FTIR spectroscopy technique. The grafted LC polymer brush was prepared via “grafting from” polymerization of 4-(6-acryloyloxyhexyloxy)benzoic acid initiated from the surface of UV-irradiated FEP substrate. The orientation under the uniaxial mechanical stress and the temperature behavior of LC brush stabilized by H-bonds were studied. Substantial changes of the structure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…For example, in a recent theoretical study concerning non-Markovian effects on entanglement between two modes interacting with an Ohmic bath, the results indicate that (under all regimes) the Markovian limit enhances a rapid decay of the correlations [46]. The approach could be particularly insightful in the elucidation of structural and dynamic relations between dangling and bound stretching modes at crystalline surfaces [47,48], and in paired states under effective coupling [49].…”
Section: Resultsmentioning
confidence: 96%
“…For example, in a recent theoretical study concerning non-Markovian effects on entanglement between two modes interacting with an Ohmic bath, the results indicate that (under all regimes) the Markovian limit enhances a rapid decay of the correlations [46]. The approach could be particularly insightful in the elucidation of structural and dynamic relations between dangling and bound stretching modes at crystalline surfaces [47,48], and in paired states under effective coupling [49].…”
Section: Resultsmentioning
confidence: 96%
“…Overall reduction in peak intensities was attributed to changes in the surface region mainly due to the erosion factor. Figure 15 showed that peaks appeared at (a) 680-780 cm À1 were due to the presence of weaker band bending for CdF group, (b) @ 980 cm À1 due to dCdCd stretch in side-chain CdCF 3 group, (c) @ 1100-1400 cm À1 for CdF coupled to CdC stretch, and (d) @2370 cm À1 for dCF 2 stretch [78][79][80].…”
Section: Vibration Spectroscopy Analysismentioning
confidence: 99%
“…Using monomers with liquid crystalline mesogenic sidegroups has proven a popular strategy, with several reports detailing this approach. [111][112][113] An alternative route is to polymerize poly(3-caprolactone) polymer brushes from gold surfaces. 114 Nematic 4-cyano-4 0 -pentylbiphenyl is then anchored to the polymer brush.…”
Section: Polymer Brushes Are Used In Areas Of Nanotechnology Includin...mentioning
confidence: 99%